2020
DOI: 10.1111/jpm.12600
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic medication side effects knowledge amongst registered mental health nurses in England: A national survey

Abstract: Accessible summary What is known on the subject? Research findings indicate the percentage of knowledge‐related errors in medicines management is high, accounting for approximately 75% of all errors, with insufficient knowledge levels one of the most significant contributors of medication errors. Patients should be able to trust nurses to engage therapeutically and actively listen to their needs and concerns, responding using skills that are helpful, providing information that is clear, accurate, meaningful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
(58 reference statements)
1
1
0
Order By: Relevance
“…Nurses report that their education did not prepare them well enough to provide psychotherapeutic intervention and standard PRN practice in mental health (Martin & Stanford, 2020). These findings concur with another two studies that indicated the limited level of pharmacology knowledge among pre‐registration students and qualified mental health nurses (Begum et al, 2020; Pearson et al, 2021). This is concerning because nurses play a vital role in medication safety.…”
Section: Implications For Healthcare Practice and Educationsupporting
confidence: 92%
“…Nurses report that their education did not prepare them well enough to provide psychotherapeutic intervention and standard PRN practice in mental health (Martin & Stanford, 2020). These findings concur with another two studies that indicated the limited level of pharmacology knowledge among pre‐registration students and qualified mental health nurses (Begum et al, 2020; Pearson et al, 2021). This is concerning because nurses play a vital role in medication safety.…”
Section: Implications For Healthcare Practice and Educationsupporting
confidence: 92%
“…Even so, Sadykov et al noted that whilst the ophthalmic complications of antipsychotic medications have been documented, few clinicians monitor for psychotropic side effects by examining the patient [9]. Additionally, studies have demonstrated that mental health and care staff have limited knowledge regarding the side effects of antipsychotic medications [10][11][12]. This subsequently influences staff understanding of the possible impact of antipsychotics on patients, the need for monitoring of the side effects of antipsychotic medications, and the importance of ensuring patients make informed decisions regarding their care [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…These discrepancies in reasons for non-adherence can be somewhat explained by understanding that practitioners can underestimate the impact taking antipsychotic medication has on quality of life [ 31 ]. For service users, adherence is a balancing act to determine if reductions in psychotic symptoms outweigh potentially debilitating side effects [ 25 ].…”
Section: Introductionmentioning
confidence: 99%